Review of group recommendation analysis and research - Yunchang WU; Baisong LIU; Yangyang WANG; Chenjie FEI (Dianxin kexue)
With the advent of age of big data,the application fields of recommendation systems have become increasingly widespread.The recommendation service object of the group recommendation systems are expanded from a single user to a group of members,and becoming one of the research hotspots in the recommendation system fields.The group recommendation system needs to consider the preferences of all group members,and to fuse the preferences of the members,and to alleviate the conflicts of preferences among them,so that the recommendation results satisfy all group members as much as possible.The recent research progress of the group recommendation was mainly reviewed.The frontiers of group classification,group detection and group prediction recommendation were summarized.And main factors of the group recommendations were generalized.Finally,the research points of group recommendation and its prospects were separately elaborated.